Pola Pengawasan Orang Tua Terhadap Aktivitas Anak di Dunia Maya : Studi Kasus Pada Keluarga dengan Anak Remaja Usia 12 – 19 Tahun di Purwokerto - Tri Nugroho Adi (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
The purpose of this study is to examine how the parent's understanding of the dangers of theinternet, how the pattern of internet parenting style of children's Internet usage, how the patternand experience of children in using the internet, and the child's perception of the pattern ofinternet parentating style. The research used qualitative description method, the data wascollected by purposive sampling from 37 parents and 37 teenagers aged 12-19 in Purwokerto byusing structured interview. The results of the study (1) parents have an understanding of internetrisks, though not all then do the protection measures; (2) the four dimensions of internet parentingstyle patterns namely mediation, introduction, restriction and coviewing. Of the four dimensions itreinforces the previous review of parental supervisory patterns namely authoritative andpermisive; (3) the majority of teenage informants have used the internet since primary school, areactive in the use of social media, the majority are classified as heavy users, and some of them haveexperience related to internet risk, children tend to agree on parental supervisory forms in internetusage but still want the existence freedom or disapproval of authoritarian supervisory patterns.